2000
DOI: 10.1016/s0014-5793(00)01581-7
|View full text |Cite
|
Sign up to set email alerts
|

EST comparison indicates 38% of human mRNAs contain possible alternative splice forms

Abstract: Expressed sequence tag (EST) databases represent a large volume of information on expressed genes including tissue type, expression profile and exon structure. In this study we create an extensive data set of human alternative splicing. We report the analysis of 7867 non-redundant mRNAs, 3011 of which contained alternative splice forms (38% of all mRNAs analysed). From a total of 12 572 ESTs 4560 different possible alternative splice forms were detected. Interestingly, 70% of the alternative splice forms corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
160
1
3

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(170 citation statements)
references
References 16 publications
6
160
1
3
Order By: Relevance
“…In all, 87% variants contained less than 16 ESTs, and 58% were represented by the EST singletons. If the singletons were excluded from the database, then only 66% genes were alternatively spliced, which is consistent with previous reports (Mironov et al, 1999;Brett et al, 2000;Kan et al, 2002).…”
Section: Asa Was Created To Identify Alternative Splicing Of Human Gesupporting
confidence: 86%
See 3 more Smart Citations
“…In all, 87% variants contained less than 16 ESTs, and 58% were represented by the EST singletons. If the singletons were excluded from the database, then only 66% genes were alternatively spliced, which is consistent with previous reports (Mironov et al, 1999;Brett et al, 2000;Kan et al, 2002).…”
Section: Asa Was Created To Identify Alternative Splicing Of Human Gesupporting
confidence: 86%
“…A higher percentage of alternative splicing (81%) than the reported ratio of 30-65% (Mironov et al, 1999;Brett et al, 2000;Kan et al, 2002) is suggested. This is mainly due to the inclusion of EST singletons in the BASD, since 58% of splicing variants are supported by one EST in our database.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The transcript was present in a variety of tissues as demonstrated by RT-PCR and also by searching for identical sequences in ESTs (http://www.ncbi.nlm.nih.gov/BLAST). Recent studies have shown that 35-38% of human RNAs contain possible alternative splice forms by comparison of multiple EST sequences (Mironov et al, 1999;Brett et al, 2000). Some of these will include exon or intron isoforms where alternative donor or acceptor sites have been used, others include skipped exons or intron retention.…”
Section: Discussionmentioning
confidence: 99%